1981
DOI: 10.1073/pnas.78.10.6221
|View full text |Cite
|
Sign up to set email alerts
|

Coordination environment of the active-site metal ion of liver alcohol dehydrogenase.

Abstract: The coordination environment of the catalytically active metal ion of horse liver alcohol dehydrogenase (alcohol:NAD+ oxidoreductase, EC 1.1.1.1) has been investigated by electron paramagnetic resonance (EPR) methods with use of the active-site-specific Co2+-reconstituted enzyme. The EPR absorption spectrum of the metal-substituted enzyme is characteristic of a rhombically distorted environment. The spectrum of the enzyme-NAD+ complex shows approximate axial symmetry of the metal ion site, indicating that bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 26 publications
4
36
1
Order By: Relevance
“…Since Co(II) has a noninteger spin and is therefore paramagnetic, EPR was a natural choice for studying the metal environment. The EPR (23,26). The observed effects of the inhibitor on the EPR spectra are consistent with Co(II) being present either in the active site or at a distance from the active site where it is influenced by gross protein conformational changes upon inhibitor binding.…”
Section: Discussionsupporting
confidence: 59%
“…Since Co(II) has a noninteger spin and is therefore paramagnetic, EPR was a natural choice for studying the metal environment. The EPR (23,26). The observed effects of the inhibitor on the EPR spectra are consistent with Co(II) being present either in the active site or at a distance from the active site where it is influenced by gross protein conformational changes upon inhibitor binding.…”
Section: Discussionsupporting
confidence: 59%
“…Yet, all experimental evidence (crystallographic and spectroscopic) agrees on that the free enzyme in the open conformation is four-coordinate [2][3]10,16,[19][20][21][22]44 . Further, it is widely assumed that the dehydration of the active site that occurs when the enzyme closes is important for the catalytic mechanism 1,2 .…”
Section: The Relative Stability Of Four-and Five-coordinate Zinc Compmentioning
confidence: 99%
“…Crystallographic and spectroscopic data showing that binding to zinc of certain bidentate inhibitors is fivecoordinate 14,15 have been taken as evidence in favor of these suggestions. Furthermore, spectroscopic studies of metal-substituted alcohol dehydrogenase have indicated that several binary and ternary complexes may be five-coordinate [6][7][8][15][16][17][18][19][20] , although other spectroscopic investigations contradict these results [21][22][23][24][25] . The kinetic evidence is also scattered and has been taken to favor fourcoordination 1,26 , as well as five-coordination 6,7,9,11,27 , of zinc in the catalytically productive ternary complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The g values obtained for Co-deuterolysin were similar to those reported for four-,ˆve-, and six-coordinated cobalt complexes including model and protein systems; some examples are the 4,5,6 compounds. [20][21][22] These complexes, including Co-deuterolysin, have mean g principal values very close to 4, higher than the freeelectron g (2.0023) and close to that of an S=3 W 2 system. 14) Hyperˆne interaction of the cobalt nucleus also is an important EPR parameter of cobalt complexes.…”
Section: Metal Center Of Deuterolysinmentioning
confidence: 99%